The Mitochondrial Aminoacyl tRNA Synthetases: Genes and Syndromes - Daria Diodato; Daniele Ghezzi; Valeria Tiranti (International Journal of Cell Biology)
Mitochondrial respiratory chain (RC) disorders are a group of genetically and clinically heterogeneous diseases. This is because protein components of the RC are encoded by both mitochondrial and nuclear genomes and are essential in all cells. In addition, the biogenesis and maintenance of mitochondria, including mitochondrial DNA (mtDNA) replication, transcription, and translation, require nuclear-encoded genes. In the past decade, a growing number of syndromes associated with dysfunction of mtDNA translation have been reported. This paper reviews the current knowledge of mutations affecting mitochondrial aminoacyl tRNAs synthetases and their role in the pathogenic mechanisms underlying the different clinical presentations.